Prevalence of alcohol and other drugs and the concentrations in blood of drivers killed in road traffic crashes in Sweden. Issue 2 (March 2014) - Ahlner, Johan; Holmgren, Anita; Jones, Alan Wayne
Background: Drunk or drug-impaired drivers represent a major public health and societal problem worldwide. Because over 95% of drivers killed on the roads in Sweden are autopsied, reliable information is available about the use of alcohol and/or other drug before the crash. Methods : This retrospective 4-year study (2008–2011) used a forensic toxicology database (TOXBASE) to evaluate the concentrations of alcohol and other drugs in blood samples from drivers killed in road-traffic crashes. Results : The mean age of all victims ( N = 895) was 48 ± 20 years, and the majority were male (86%). In 504 drivers (56%), the results of toxicological analysis were negative and these victims were older; mean age (± SD) 47 ± 20 years, than alcohol positive cases (35 ± 14 years) and illicit drug users (34 ± 15 years). In 21% of fatalities, blood-alcohol concentration (BAC) was above the statutory limit for driving (0.2 g/L), although the median BAC was appreciably higher (1.72 g/L). Illicit drugs (mainly amphetamine and cannabis) were identified in 7% of victims, either alone (2.5%), together with alcohol (1.8%) or a prescription drug (2%). The psychoactive prescription drugs identified were mainly benzodiazepines, z-hypnotics and tramadol, which were found in the blood of 7.6% of crash victims. Conclusions : The high median BAC in fatally-injured drivers speaks strongly towards alcohol-induced impairment as being responsible for the crash. Compared with alcohol, the prevalence of illicit and psychoactive prescription drugs was fairly low despite a dramatic increase in the number of drug-impaired drivers arrested by the police after a zero-tolerance law was introduced in 1999 .